The Future of the Superfund: Where is it Headed and How Will it Get There? (Hinckley Journal of Politics; Vol 7 (2006), 2017)
This paper is a critical analysis of the Environmental Protection Agency’s Superfund program, turned 25 last year. This paper will provide a historical overview of the program’s development in managing environmental contamination. It will also discuss the more recent problems the program finds itself addressing. The corporate taxes that helped finance the Superfund Trust Fund expired in 1995. Now the question is: does the cleanup program still need $1.4 billion a year, or is it time to start cutting appropriations as the list of sites are completed? This paper will challenge the belief that current funding levels are sufficient to complete the cleanup of the remaining contaminated sites that exist throughout the nation. Specifically, five assumptions of those who argue for fewer appropriations will be thoroughly examined.